HUBUNGAN PEMBELAJARAN MATEMATIKA DENGAN PENGEMBANGAN LIFE SKILLS SISWA SEKOLAH DASAR - Afriani Lubis, Rini; Marzuqo, Khusnal; Maidiana Ardini, Deva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between mathematics learning and the development of life skills among elementary school students. This research used a quantitative approach with a correlational method. The subjects were 28 fifth-grade students selected using purposive sampling. Data were collected through life skills questionnaires and classroom observations to obtain comprehensive information about students’ learning activities and skills development. Data analysis used Pearson Product Moment correlation test to examine the relationship between the two variables. The results showed a positive and significant relationship between mathematics learning and students’ life skills with r value 0.62 > r table 0.374 and significance value 0.001 < 0.05. This indicates that better and more effective mathematics learning leads to better development of students’ life skills in elementary school, especially in critical thinking, problem-solving, cooperation, and communication abilities.